Comparison of macrofungi communities anti examination of macrofungi-plant interactions in forest stands in North Hungary - Benedek, L.; Pál-Fám, F.; Nagy, J. (International Journal of Horticultural Science, 2005)
Parallel phyto- and mycocoenological investigations have been made since 2001 in all characteristic forest types in Borzsony Mts., North Hungary. The main aim of this work was the examination of similarities between plant and fungal communities, as well as the plant—fungi connections within certain habitats. Among the total 381 macrofungi species documented, 330 occurred in the investigated 7 forest stands. Wood-inhabiting fungal communities of coniferous stands can be separated unambiguously from those of deciduous stands. Communities of deciduous stands can be divided into two subgroups: those fructifying in wet and in semidry stands. The main factors which influence the composition of wood inhabiting fungal communities seem to be, in decreasing order: (1) crown layer composition; and (2) soil properties (probably only humidity). Wood-inhabiting fungal communities do not show any relation with the underwood layer of particular plant associations. Amongst soil inhabiting fungal communities, three groups can be separated: (1) those of coniferous stands and alderwood; (2) those of the two climax stands; and (3) those of the two edaphic deciduous stands. Classification of these communities is similar to classification of plants of underwood layers. Probably both are dependent upon soil properties (humidity and pH) of particular habitats, but the range of mycorrhizal partners is also decisive for macrofungi communities. All investigated stands are under forestry management, with low quantity of dead and infected wood, so forestry management type may have a great influence in composition of both wood and soil saprotrophic fungal communities.